Modulated phase of an Ising system with competing interactions on a Cayley Tree of arbitrary order - Uguz, Selman; Ganikhodjaev, Nasir; Temir, Seyit; Akin, Hasan (American Institute of Physics, 2010)
We study the phase diagram for Ising model on a Cayley tree of arbitrary order k with competing nearest‐neighbor interactions J1 and prolonged next‐nearest‐neighbor interactions Jp. To perform this study, an iterative scheme similar to that appearing in real space renormalization group frameworks is established; it recovers, as particular case, previous work by Vannimenus for k  =  2